Allocation Of Working Time Of Rice Farmer's Household Gender Perspective in Tanah Miring District Kabupaten Merauke - Suroto Suroto (Media Ekonomi dan Manajemen, 2019)
This research aims to analyze: work time allocation and the factors that influence the allocation of working time on the farming of rice made by man (husband) and (wife) women and the role of gender occurring within the household. The analytical approach used the model of average tabulation, multiple linear regression analysis, and gender analysis of the Harvard Model. This research used cross section data with a sample of 100 males (husbands) and 100 females (wives) of households of rice farmers. The results of research showed that the amount of working time allocation for male (husband) is greater than the allocation of working time of female (wife). Work time allocation the man (husband) influenced by land area and the amount of production.Women's work time allocation (wife) are affected by land area, level of education, and the number of family members.Gender analysis results show the man (husband) more productive activities and on the role of the woman (wife) on reproductive activities.Access and control in the household more done by men (husbands).The factors that provide a positive impact, namely the demographic structure of the region, institution/economic factors, the training performed by government institutions, and the attitude of the society that received intervention from outside.The factors which provide negative effects namely the norms of the community, and the local customary law.